2011
DOI: 10.4137/cmamd.s5951
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peroxisome Proliferator-Activated Receptor Gamma Agonist (Pioglitazone) and Methotrexate on Disease Activity in Rheumatoid Arthritis (Experimental and Clinical Study)

Abstract: Objective:To investigate the combined effect of both pioglitazone and methotrexate on disease activity of rheumatoid arthritis in a biphasic study; experimental and clinical.Methods:Experimentally: 50 rats were divided into 5 equal groups; controls, experimental arthritis, methorexate treated (0.1 mg/Kg daily), pioglitazone-treated (10 mg/kg daily), and methotrexate and pioglitazone treated. Clinically: forty-nine diabetic rheumatoid arthritis patients were included. Patients group consisted of 28 patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 46 publications
4
40
0
1
Order By: Relevance
“…Accordingly, PPARɤ ligands have shown to have an anti-inflammatory activity in a variety of experimental and clinical studies of acute and chronic inflammation [32]. The present work comes in agreement with Dina et al (2011), who demonstrated that clinically, pioglitazone treatment showed significant improvement of CRP levels [33].…”
Section: Discussionsupporting
confidence: 95%
“…Accordingly, PPARɤ ligands have shown to have an anti-inflammatory activity in a variety of experimental and clinical studies of acute and chronic inflammation [32]. The present work comes in agreement with Dina et al (2011), who demonstrated that clinically, pioglitazone treatment showed significant improvement of CRP levels [33].…”
Section: Discussionsupporting
confidence: 95%
“…In response to loads at 0.2 and 0.5 N, elbow loading reduced the expression and activities of MMP-1 and MMP-13. On the contrary, it increased their mRNA and degenerative activity levels by higher loads at 2 N. We have previously shown that a natural joint rotation decreases enzyme activities of collagenases [12]. To our knowledge, this study demonstrated for the first time that moderate lateral loads to the synovial joint can suppress degenerative actions of MMPs in the articular cartilage.…”
Section: Discussionmentioning
confidence: 52%
“…Osteocalcin is an anabolic bone marker [11], which served to validate the efficacy of elbow loading in bone formation in the ulna. CITED2 is a transcription regulator that is reported to suppress the expression of MMP-1 and MMP-13 [12]. To evaluate various degenerative activities of MMPs, we determined total activities of collagenases and total activities of gelatinases, as well as MMP-1- and MMP-13-selective activities.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, pioglitazone decreased inflammatory-bone destruction and reduced bone micro-architecture in AIA rats by controlling circulating and local expression of IL-17 with a subsequent decrease of the (RANKL/OPG) ratio [13]. Of interest, three recent studies have demonstrated the efficacy of pioglitazone alone or in combination with methotrexate in RA patients [14][15][16].…”
Section: Discussionmentioning
confidence: 99%